A new approach to the mechanics of metal cutting - Oxley, P. L. B. (College of Aeronautics, 1964)
Introduction A number of equations have been derived for predicting the shear angle (0 in Fig. 1) in orthogonal metal cutting. The best known of these is due to Merchant (1) who by assuming that the value of shear angle would be such as to give a minimum expenditure of work obtained the relation … [cont.].